Neoadjuvant chemotherapy or chemoradiotherapy plus sintilimab versus neoadjuvant chemoradiotherapy for locally advanced oesophageal squamous cell carcinoma: a study protocol of a multicentre, randomised, controlled, phase III trial (SCIENCE study) - Haining Zhou; Qiang Fang; Yongtao Han; Long Liang; Peng Tang; Lin Peng; Wenwu He; Yehan Zhou; Jiahua Lv; Xuefeng Leng; Hansong Bai; Tongchen Hu; et al. (BMJ Open)
Introduction Oesophageal squamous cell carcinoma (ESCC) is a globally challenging digestive tract malignancy with poor prognosis and limited treatment options. Early-stage ESCC is often asymptomatic, leading to a late-stage diagnosis in many cases. Neoadjuvant therapy combined with surgery is the standard treatment approach for locally advanced ESCC. In recent years, immunotherapy has shown significant efficacy in ESCC. However, various neoadjuvant treatment regimens, including chemotherapy, radiotherapy and immunotherapy, have produced inconsistent outcomes. This study aims to evaluate the efficacy and safety of neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiotherapy (nCRT) combined with immunotherapy compared with nCRT alone.Methods and analysis This is a prospective, multicentre, randomised, controlled phase III trial enrolling 420 patients with locally advanced thoracic ESCC. Patients will be randomly assigned (1:1:1) into three groups: (A) nCT plus sintilimab, (B) nCRT plus sintilimab or (C) nCRT alone. The primary endpoints are pathological complete response and event-free survival. Secondary endpoints include the objective remission rate, disease control rate, R0 resection rate, major pathological remission rate, disease-free survival, overall survival, patient quality of life and patient-reported outcomes. Data will be analysed using both the intention-to-treat and per-protocol approaches, with multiple imputation methods for handling missing data.Ethics and dissemination The study has been approved by the Ethics Committee for Medical Research and New Medical Technology of Sichuan Cancer Hospital (approval number: SCCHEC-02-2022-108). Written informed consent will be obtained from all participants. The findings will be disseminated through peer-reviewed journals and conference presentations.Trial registration number NCT05244798